Вы находитесь на странице: 1из 20

# Problems

P17.2-1

P17.2-2

1
P17.2-3

## − z21 I1 −I2 z21

I2 = ⇒ Ai = = (forward current gain)
z22 + R L I1 z22 + R L
V1 z11 I1 + z12 I 2 z A I z z
R in = = = z11 − 12 i 1 = z11 − 12 21 (input resistance)
I1 I1 I1 ( z22 + R L )
V2 Ai R L
V2 = − I 2 R L = Ai R L I1 and V1 = R in I1 ⇒ Av = = (forward voltage gain)
V1 R in
RL
∴ Ap = Ai Av = Ai2
R in

P17.2-4
First, simplify the circuit using a Δ-Y transformation:

R1
R eq = || R = 5 || 20 = 4 Ω
3
Mesh equations:
30 = 18 I −10 I 2
50 = 10 I − 20 I 2
Solving for the required current:
30 −10
50 − 20 −100
I= = = 0.385 A
18(−20) − (−10)10 −260

2
P17.2-5

3
Section 17-3: Equations of Two-Port Networks

P17.3-1

Z 12 = 6 Ω
Z 11 − Z 12 = 12 Ω ⇒ Z 11 = 18 Ω
Z 22 − Z 21 = 3 Ω ⇒ Z 22 = 9 Ω

⎡18 6⎤
Z = ⎢ Ω
⎣6 9 ⎥⎦

I1 1
Y11 = = S
V1 V =0 14
2

I1 −6 I 2 1
Y12 = = = − S = Υ 21
V2 V1 = 0
(6+12) V2 21
I2 V2 / 7 1 ⎡1
Y 22 = = = S −1 ⎤
V2 V1 = 0
V2 7 Υ= ⎢ 14 21⎥
S
⎢− 1 1 ⎥
⎣ 21 7 ⎦

P17.3-2

z 12 = z 21 = − j 4 Ω
z 11 − z 12 = 2 Ω ⇒ z 11 = 2 − j 4 Ω
z 22 − z 21 = j 2 Ω ⇒ z 22 = j 2 − j 4 = − j 2 Ω

⎡2− j 4 − j4 ⎤
Z = ⎢ Ω
⎣− j 4 − j 2 ⎥⎦

1
P17.3-3

I1 I2
Y11 = and Y 21 =
V1 V2 = 0
V1 V2 = 0

I1 + I 2 I+I I
V1 = and 1 2 + 2 = bV1
G1 G1 G2
so
I1 = (G1 −(b −1) G2 ) V1 = −1 V1 and I 2 = (b −1) G2 V1 = 3 V1
Finally
Y11 = −1 S and Y 21 = 3 S
Next

I1+I 2 −I 2
V2 = and V 2 =
G3 G2

I1
Y12 = = −G 2 = − 1 S
V2
V1 = 0

I2
Y 22 = = G2 + G3 = 4 S
V2
V1 = 0

P17.3-4
Using Fig. 17.3-2 as shown:

## −Y12 = −Y21 = 0.1 S or Y12 = Y21 = −0.1 S

Y11 = 0.2 − Y12 = 0.3 S
Y22 = 0.05 − Y21 = 0.15 S

P17.3-5
Y12 = −10 μ S = Y 21
Y11 +Y12 =13.33 μ S
Y11 = 23.33 μ S

Y 22 + Y 21 = 20 μS ⇒ Y 22 = 30 μS

2
P17.3-6

V1
Z 11 = = 3 + j 3 − j 2 = (3+ j ) Ω
I1 I2 = 0

V2 − j 2 I1
Z 21 = = = − j2 Ω
I1 I2 = 0
I1

V1
Z 12 = = − j2 Ω
I2 I1 = 0

V2
Z 22 = = − j2 Ω
I2 I1 = 0

P17.3-7

Z 11− Z 21 = 4 ⎫
⎪ 1 4 s +1
1⎬ ⇒ Z 11 = 4 + =
Z 21 − Z 12 = ⎪ s s
s⎭
1 2 s 2 +1
Z 22 − Z 21 = 2 s ⇒ Z 22 = 2 s + =
s s

P17.3-8
Given:
⎡ s +1 ⎤
⎢ −1 ⎥
Y= s
⎢ ⎥
⎣ −1 s +1⎦

## Try a π circuit as shown at the right.

Y12 = Y 21 = −1 S
1 1 s +1
Y11 +Y 12 = ⇒ Y11 = −1 =
s s s
Y 22 + Y 21 = s ⇒ Y 22 = s − ( −1) = s + 1

3
P17.3-9
Given: Try :
⎡ s + 2s + 2
2
1 ⎤
⎢ s 2 + s +1 s + s +1 ⎥⎥
2
Z= ⎢
⎢ 1 s 2 +1 ⎥
⎢⎣ s 2 + s +1 s 2 + s +1 ⎥⎦

## From the circuit, we calculate:

1
Cs
( R2 + L s ) R2 + L s L C R1 s 2 + ( R1 R 2 C + L ) s + R1 + R 2
z 11 = R1 + = R1 + =
1
+ R2 + L s 1 + R 2 C s + L C s 2
L C s2 + R2 C s + 1
Cs

## Comparing to the given z 11 yields:

LC =1 ⎫
⎪ ⎧ R1 = 1 Ω
R2 C = 1 ⎪ R =1 Ω
⎪⎪ ⎪
L C R1 = 1 ⎬ ⇒ ⎨ 2
R1 R 2 C + L = 2 ⎪ ⎪ L =1 H
⎪ ⎪⎩ C = 1 F
R1 + R 2 = 2 ⎪⎭

Then check z 12 , z 21 and z 22 . The are all okay. If they were not, we would have to try a different
circuit structure..

P17.3-10
It is sufficient to require that the input resistance of each section of the circuit is equal to Ro, that
is

Then
R (2 R + Ro )
Ro = ⇒ Ro = − R ± R 2 + 2 R 2 = − R ± 3 R = ( 3 −1) R
3 R + Ro

4
5
Section 17-4: Z and Y Parameters

P17.4-1

V1 (b + R1 )
i=− and I 2 = − V1
R1 R1 R 2
⎛ b + R1 + R 2 ⎞
I1 = − I 2 − i = ⎜ ⎟⎟ V1
⎜ R1 R 2
⎝ ⎠

I1 b + R1 + R 2 I2 (b + R1 )
Y11 = = and Y21 = =−
V1 V2 = 0
R1 R 2 V1 V2 = 0
R1 R 2

I 2 = − I1
V2
V2 = R 2 I 2 ⇒ I2 =
R2

I2 1 I1 1
Y22 = = and Y12 = =−
V2 V1 = 0
R2 V2 V1 = 0
R2
Finally
⎡ b+ R 1 + R 2 1 ⎤
⎢ − ⎥
⎢ R1 R 2 R2 ⎥
Y=⎢ ⎥
b+ R 1
⎢ − 1 ⎥
⎢ R1 R 2 R 2 ⎥⎦

P17.4-2

⎧⎪ v1 = (1 + 3) i1 = 4 i1
i2 = 0 ⇒ ⎨
⎪⎩ v 2 = 3 i1
therefore
Z 11 = 4 Ω and Z 21 = 3 Ω

1
⎧ v1 = 3 (α i 2 + i 2 )

i1 = 0 ⇒ ⎨
⎪⎩ v1 = 3 (α i 2 + i 2 ) + 2 i 2
therefore
Z 12 = 3 (1 + α ) and Z 21 = 5 + 3α
Finally,
⎡4 3(1+α ) ⎤
Z= ⎢
⎣3 5+3α ⎥⎦

P17.4-3
Treat the circuit as the parallel connection of two 2-port networks:

## The admittance matrix of the entire network

can be obtained as the sum of the admittance
matrices of these two 2-port networks

⎡1 0 ⎤ ⎡ 2 s − s ⎤ ⎡1+ 2 s − s ⎤
Y=⎢ ⎥+⎢ ⎥=⎢
⎣ 2 1⎦ ⎣ − s 2 s ⎦ ⎣ 2 − s 1+ 2 s ⎥⎦

When i1 ( t ) = u ( t ) :
⎡ 2 s +1 s ⎤
⎡ 1⎤ ⎡ 1⎤ ⎢ ⎡1⎤
⎡V ( s ) ⎤ ⎡V ( s ) ⎤ s − 2 2 s +1⎥⎦
Y ⎢ 1 ⎥ = ⎢ s ⎥ ⇒ ⎢ 1 ⎥ = Y −1 ⎢ s ⎥ = ⎣ 2 ⎢s⎥
⎣V2 ( s ) ⎦ ⎢ 0 ⎥ ⎣V2 ( s ) ⎦ ⎢ ⎥ 3 s + 6 s +1 ⎢ ⎥
⎣ ⎦ ⎣0 ⎦ ⎣0 ⎦
so
( S − 2) 1 ⎡ −6 −1.25 7.25 ⎤
V2 ( s ) = = ⎢ + +
S (3 S + 6 S +1)
2
3 ⎣ s S + 1.82 S + 0.184 ⎥⎦

## Taking the inverse Laplace transform

1
v2 (t) = ⎡ −6−1.25 e −1.82 t + 7.25 e − 0.184 t ⎤⎦
⎣ t ≥0
3

2
P17.4-4

KVL:
1
2
( i1 − v 1 ) + 2 v 2 + v 2 − v 1 = 0
KCL: i1 − v 1 = 4 v 1 + 2 v 2

⎧ i1 − 5 v 1 v1 2
⎪ i1 = 3v1 − 6 ⇒ z 11 = = Ω
i1 = 3v1 − 6 v 2 ⎫ ⎪ 2 i1 9
⎬ ⇒ ⎨
i1 = 5 v1 + 2 v2 ⎭ ⎪i = 5 i1 + 6 v 2 + 2 v ⇒ z = v 2 = − 1 Ω
⎪1 3
2 21
i1 18

1 13
KVL: v 2 = 1 v1 + v1 + 5 v1 = v1
2 2

v2
KCL: i2 = + 5 v1 = 2 v 2 + 5 v1
12

⎛ 13 ⎞ 1
i 2 = 2 ⎜ v1 ⎟ + 5 v1 = 18 v1 ⇒ z 12 = Ω
⎝ 2 ⎠ 18
and
⎛ 2 ⎞
i 2 = 2 v 2 + 5 ⎜ v 2 ⎟ = 2.769 v 2 ⇒ z 22 = 0.361 Ω
⎝ 13 ⎠

3
P17.4-5

v1
KCL: i1 + i 2 =
R1
KVL: − R 2 i 2 − b v1 + 0 − v1 = 0

Then
b +1 ⎛ 1 b +1⎞ R 2 + R1 ( b + 1)
i2 = − v1 and i1 = ⎜ + ⎟ v1 = v1
R2 ⎜ R1 R 2 ⎟ R R
⎝ ⎠ 1 2

so
i2 b +1 i1 R 2 + R1 ( b + 1)
y 21 = =− and y 11 = =
v1 R2 v1 R1 R 2

1
KVL: R 2 i1 + v 2 = 0 ⇒ i1 = − v2
R2

⎛ 1 ⎞
KCL: v 2 = R 3 ( i1 + i 2 ) = R 3 ⎜ − v 2 ⎟ + R3 i 2
⎜ R2 ⎟
⎝ ⎠

Then
i1 1 ⎛ R3 ⎞ i2 1 1
y 12 = =− and v 2 ⎜ 1 + = R3 i 2 ⇒ y 22 = = +
v2 R2 ⎜ R 2 ⎟⎟ v2 R3 R 2
⎝ ⎠

Finally
⎡ R 2 + R 1 ( b +1) 1 ⎤
⎢ − ⎥
⎢ R1 R 2 R2 ⎥
Y=⎢
⎢ b +1 R 2 + R 3 ⎥⎥

⎢ R2 R 2 R 3 ⎥⎦

4
Section 17-5: Hybrid Transmission Parameters

P17.5-1

V1 34 V1 5
B= = = 6.8 Ω since − I 2 = = V1
−I2 V2 = 0
5 2 + 4||10 34

I1 10 + 4 10
D= = = 1.4 since I2 = − I1
−I2 V2 = 0
10 10 + 4

V1 12 10
A= = = 1.2 since V2 = V1
V2 I2 =0
10 10 + 2

I1 1
C= = = 0.1 S
V2 I2 =0
10

P17.5-2
V2 = 0
so
V1 = ( R i + R1 || R 2 ) I 1
therefore

V1
h11 = = R i + R1 || R 2 = 600 kΩ
I1
V2 = 0

KVL:
R1 Ri
I2 + I1 = − A I1
R1 + R 2 Ro
therefore
I Ri R1
h 21 = 2 = −( A + ) = −106
I1 Ro R1 + R 2
V2 = 0

1
I 1 = 0 ⇒ vi = 0 ⇒ A vi = 0
so
V2
I2 =
R o ( R1 + R 2 )
therefore
I2 R o + R1 + R 2
h 22 = = = 10−3
V2 R o ( R1 + R 2 )
I 1 =0

Next,
R1
V1 = V2
R1 + R 2
therefore
V1 R1 1
h12 = = =
V2 R1 + R 2 2
I 1 =0

P17.5-3
Compare : to
V 2 = n V1 V1 = h11 I 1 + h12V 2
I 1 =−n I 2 I 2 = h 21 I 1 + h 22V 2

## Then h11 = 0, h 22 = 0, h12 = 1 and h 21 = 1

n −n

P17.5-4
R2 R3
V1 = ( R1 + R 2 || R 3 ) I 1 ⇒ h11 = R1 +
R 2 +R 3
R2 R2
I2 = − I 1 ⇒ h 21 = −
R 2 +R 3 R 2 +R 3

V2 1
I2 = ⇒ h 22 =
R 2 +R 3 R 2 +R 3
R2 R2
V1 = V 2 ⇒ h12 =
R 2 +R 3 R 2 +R 3

2
P17.5-5

## I 2 = 0.1v and v = 950 I 1

so I 2 = 95 I 1

V1
h11 = = 50 + 950 = 1000 Ω
I1
V2 = 0

I2
h 21 = = 95
I1
V2 = 0

I1 = 0 ⇒ v = 0

V1
h12 = =0
V2
I1 = 0

I2
h 22 = = 10−4 S
V2
I1 = 0

3
Section 17.6: Relationships between Two-Port Parameters

P17.6-1
⎧ I1 = Y11 V1 + Y12 V2 ⎧⎪V1 = h11 I1 + h12 V2
Y parameters: ⎨ and H parameters: ⎨
⎩ I 2 = Y21 V1 + Y22 V2 ⎪⎩ I 2 = h 21 I1 + h 22 V2
Solve the Y parameter equations for V1 and I 2 to put them in the same form as the H parameter
equations.

−1
−Y11 V1 + I1 = Y12 V2 ⎡ −Y11 0 ⎤ ⎡V1 ⎤ ⎡ −1 Y12 ⎤ ⎡ I1 ⎤ ⎡V1 ⎤ ⎡ −Y11 0⎤ ⎡ −1 Y12 ⎤ ⎡ I1 ⎤
⇒ ⎢ ⎥ ⎢ ⎥ =⎢ ⎢ ⎥ ⇒ ⎢ ⎥=⎢ ⎥
−Y21 V1 + I 2 = Y22 V2 ⎣ −Y21 1⎦ ⎣ I 2 ⎦ ⎣0

Y22 ⎦ ⎣V2 ⎦ ⎣ I 2 ⎦ ⎣ −Y21 1 ⎦
⎢0
⎣ Y22 ⎥⎦ ⎢⎣V2 ⎥⎦

⎡ 1 ⎤ ⎡1 Y12 ⎤
− 0⎥ −
⎡ −1 Y12 ⎤ ⎢ Y11 ⎡ −1 Y12 ⎤ ⎢ Y11 ⎥
−1
⎡ −Y11 0 ⎤ Y11
∴H = ⎢ ⎥ ⎢ = ⎢ ⎥ ⎢ =⎢ ⎥
⎣ −Y21 1 ⎦ ⎣0 Y22 ⎦⎥ ⎢ Y21 ⎥ ⎣0 Y22 ⎦⎥ ⎢ Y21 Y12Y21 ⎥
⎢− Y 1⎥ ⎢Y Y22 −
Y11 ⎥⎦
⎣ 11 ⎦ ⎣ 11

P17.6-2
⎡ Z 22 Z 12 ⎤ ⎡ 6 2 ⎤
⎢ ΔZ − ⎥ ⎢ − ⎥
First ΔZ = (3)(6) − (2)(2) = 14 . Then Y = ⎢ ΔZ ⎥ 14 14 .
=⎢ ⎥
⎢ − Z 21 Z 11 ⎥ ⎢ − 2 3⎥
⎢⎣ ΔZ ΔZ ⎦⎥ ⎢⎣ 14 14 ⎥⎦

P17.6-3
⎡1 Y12 ⎤
⎢ Y − Y ⎥ ⎡10 −1 ⎤
First ΔY = (0.1)(0.5) − (0.4)(0.1) = .01 S . Then H = ⎢ 11 11
⎥ =
Y ⎥ ⎢⎣ 4 0.1⎥⎦
.
⎢ 21
Y Δ
⎢Y Y11 ⎥⎦
⎣ 11

P17.6-4
⎡ 1 Y12 ⎤
⎢ Y - Y ⎥ ⎡ 2 0.8 ⎤
First ΔY = (0.5)(0.6) − (−0.4)(−0.4) S . Then H = ⎢ ⎥ =
11 11

## ⎢ Y21 ΔY ⎥ ⎢⎣ −0.8 0.28⎥⎦

⎢Y Y11 ⎥⎦
⎣ 11

1
Section 17.7: Interconnection of Two-Port Networks

P17.7-1
Y12 = Y21 = − 1 S
3
⎡4 − 1 ⎤
Ya = ⎢
Y22 = 0 − Y21 = 1 S 3 3⎥
3 ⎢− 1 1 ⎥
Y11 + Y12 = 1 S ⇒ Y11 = 4 S ⎣ 3 3⎦
3

Y12 = Y21 = −1 S ⎡3 −1 ⎤
Yb = ⎢ 2 ⎥
Y11 + Y12 = 1 S ⇒ Y11 = 3 S ⎢ −1 4 ⎥
2 2
⎣ 3⎦
Y21 +Y22 = 1 S ⇒ Y22 = 4 S
3 3

⎡( 4 + 3 ) − 4 ⎤ ⎡17 −4 ⎤
Y = Ya + Yb = ⎢ 3 2 3⎥ ⎢ 6
=
3⎥
⎢ −4 5 ⎥ ⎢ −4 5 ⎥
⎣ 3 3 ⎦ ⎣ 3 3⎦

P17.7-2

⎡ 10 −6 ⎤ ⎡ 8 44 ⎤
⎢ 44 44 ⎥ ⎢6 6 ⎥
Y=⎢ ⎥ T=⎢ ⎥
⎢ −6 8 ⎥ ⎢ 1 10 ⎥
⎢⎣ 44 44 ⎥⎦ ⎢⎣ 6 6 ⎥⎦

⎡ 20 −12 ⎤
⎢ 44 44 ⎥
Yp = Y + Y = ⎢ ⎥
⎢ −12 16 ⎥
⎣⎢ 44 44 ⎦⎥

1
⎡108 792 ⎤
⎢ 36 36 ⎥
TC = T ⋅ T = ⎢ ⎥
⎢ 18 144 ⎥
⎢⎣ 36 36 ⎥⎦

P17.7-3
⎡ 1 ⎤
⎢ s L + s C −s C ⎥ ⎡G1 + G 2 −G 2 ⎤
Y = Ya + Yb = ⎢ ⎥ + ⎢ ⎥
⎢ 1 ⎥ ⎢⎣ −G 2 G 2 +G 3 ⎦⎥
⎢−s C + sC⎥
⎣ sL ⎦

2
Section 17.8 How Can We Check…?
P17.8-1

⎛ 75 ⎞
V1 = 50 ⎜ ⎟ I 2 = 15 I 2
⎝ 175+ 75 ⎠

V1
Z 12 = = 15 Ω
I2 I1 = 0

⎛ 1 1 ⎞
I1 = ⎜ + ⎟ V1 = 0.028 V1
⎝ 50 125 ⎠

I1
Y11 = = 28 mS
V1 V2 = 0

P17.8-2

## V1 = (2 + 0.2 s ) I1 ⎫ Z 11 = 2 + 0.2 s = 0.2 ( s +10)

⎬⇒
V2 = (0.1 s ) I1 ⎭ Z 21 = 0.1 s

## ΔZ = (2 + 0.2 s )(2 + 0.2 s) − (0.1 s)(0.1 s ) = 0.01(3 s 2 + 80 s + 400)

1
⎡ Z11 ΔZ ⎤ ⎡ 2( s +10) 0.1(3 s 2 +80 s + 400) ⎤
⎢Z Z 21 ⎥ ⎢ ⎥
T= ⎢ 21 ⎥=⎢ s s ⎥
⎢ 1 Z 22 ⎥ ⎢ 10 2 ( s +10) ⎥
⎢Z Z 21 ⎥⎦ ⎢⎣ ⎥⎦
⎣ 21 s s